Conceptualising Animal Abuse with an Antisocial Behaviour Framework - Eleonora Gullone (Animals, 2011)
This paper reviews current findings in the human aggression and antisocial behaviour literature and those in the animal abuse literature with the aim of highlighting the overlap in conceptualisation. The major aim of this review is to highlight that the co-occurrence between animal abuse behaviours and aggression and violence toward humans can be logically understood through examination of the research evidence for antisocial and aggressive behaviour. From examination through this framework, it is not at all surprising that the two co-occur. Indeed, it would be surprising if they did not. Animal abuse is one expression of antisocial behaviour. What is also known from the extensive antisocial behaviour literature is that antisocial behaviours co-occur such that the presence of one form of antisocial behaviour is highly predictive of the presence of other antisocial behaviours. From such a framework, it becomes evident that animal abuse should be considered an important indicator of antisocial behaviour and violence as are other aggressive and antisocial behaviours. The implications of such a stance are that law enforcement, health and other professionals should not minimize the presence of animal abuse in their law enforcement, prevention, and treatment decisions.